2016
DOI: 10.1039/c5ra19066e
|View full text |Cite
|
Sign up to set email alerts
|

Role of graphene oxide as a heterogeneous acid catalyst and benign oxidant for synthesis of benzimidazoles and benzothiazoles

Abstract: Graphene oxide plays a dual role as active metal-free acid catalyst and as non-toxic oxidant for benzothiazole and benzimidazole synthesis. Isolated partially reduced graphene oxide was re-oxidized to regenerate the catalyst and restore its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…XRD pattern of GO and VO‐ f ‐GO catalyst depicted in the Figure S2. Typically, XRD pattern of graphite shows only a single characteristic peak at 2θ = 26°, however, on addition/insertion of oxygenated functional groups onto the surface by oxidation process this peak was lessened significantly and a new characteristic peak at 2θ = 10.8° was emerged out . This charateristic peak was due to oxidative functional groups which was experienced reduction on further modification due to functionalization at hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…XRD pattern of GO and VO‐ f ‐GO catalyst depicted in the Figure S2. Typically, XRD pattern of graphite shows only a single characteristic peak at 2θ = 26°, however, on addition/insertion of oxygenated functional groups onto the surface by oxidation process this peak was lessened significantly and a new characteristic peak at 2θ = 10.8° was emerged out . This charateristic peak was due to oxidative functional groups which was experienced reduction on further modification due to functionalization at hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation of GO on reaction has been reported in previous studies was not observed in the reaction. GO can also act as an oxidizing agent donating oxygen causing a decrease in zeta potential of GO promoting aggregation . No indication of partial reduction of catalyst, a primary cause of loss of GO activity, is observed, as the catalyst does not exhibit any tendency for aggregation even after 4 th reuse and the colour of the catalyst remains brown, which indicates GO does not undergo self‐reduction or behave as behave as an oxidising agent.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of oxidation will have a significant effect on the catalytic ability of GO. Graphene oxide has previously been shown to catalyse nucleophilic addition of amino groups to aldehydes . Here we investigated the activity of GO for catalysing multicomponent Biginelli reaction for synthesis of dihydropyrimidinones from ethylacetoacetate, aromatic aldehydes and urea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations